The Information Society—Using New (and Old) Media to Learn about New (and Old) Media - Downey, Greg; Johnson, Nathan; Roberts, Sarah (My University, 2009)
This session will discuss the course design, instructional technologies, and classroom experiences from a new hybrid online/offline introductory undergraduate course, LIS 201: The Information Society. We encourage candid and critical discussion about the boundaries between in-person and online instruction, the appropriate use of digital technology for writing and speaking training and collaboration, and the perils and promise of teaching about technology using that technology. Participants will be inspired to think about ways to weave collaborative online tools like weblogs, wikis, and podcasts into writing and speaking assignments and consider the merits and risks of structuring new classes in a hybrid in-person/online format for full-time resident undergraduate students
Presentation for the Symposium for Teaching and Learning Excellence, University of Wisconsin-Madison, 26 February 2009.